(untitled) (Revista Lusófona de Educação, 2014)
Recensão Crítica à obra de António Teodoro e Manuela Guilherme European and Latin American Higher Education Betwwen Mirrors. Conceptual Framewoks and Policies of Equity and Social Cohesion.